2006
DOI: 10.1111/j.1540-8175.2006.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Left Ventricle Performance from Two Dimensional Echo Images

Abstract: This work concludes that the regional and global left ventricle systolic dysfunction can be assessed by the ER measured at end-diastole and end-systole from 2D echocardiogram and may contribute to the high rate of cardiovascular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…As expected, the hybrid patients had a higher regurgitant fraction versus the NW‐RV‐PA since the latter cohort does not have a “run‐off” shunt, but had a lower regurgitant fraction compared to the NW‐BT who do have a “run‐off” through the modified BT shunt 9 . The eccentricity index showed a less spherical RV for the hybrid patients, which theoretically should be better for these patients 18–20 . The RV % change and CI results were discrepant between the hybrid patients versus the NW‐BT/RV‐PA patients with the RV% change being higher and the CI being lower, but all values were within normal range.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…As expected, the hybrid patients had a higher regurgitant fraction versus the NW‐RV‐PA since the latter cohort does not have a “run‐off” shunt, but had a lower regurgitant fraction compared to the NW‐BT who do have a “run‐off” through the modified BT shunt 9 . The eccentricity index showed a less spherical RV for the hybrid patients, which theoretically should be better for these patients 18–20 . The RV % change and CI results were discrepant between the hybrid patients versus the NW‐BT/RV‐PA patients with the RV% change being higher and the CI being lower, but all values were within normal range.…”
Section: Discussionmentioning
confidence: 67%
“…9 The eccentricity index showed a less spherical RV for the hybrid patients, which theoretically should be better for these patients. [18][19][20] The RV % change and CI results were discrepant between the hybrid patients versus the NW-BT/ RV-PA patients with the RV% change being higher and the CI being lower, but all values were within normal range. Caution must obviously be made comparing measurements from two different institutions because of the inherent pitfalls, but these values do give a starting point for much needed future studies comparing these respective surgical pathways.…”
Section: Discussionmentioning
confidence: 91%
“…In older patients with normal LVEF, concentric geometry is associated with lower MFS, implying decreased myocardial contractile function 25 . The study of left ventricle geometry allows quantitative evaluation of ventricle performance from M‐B mode echo images 26 . The disparity between midwall and endocardial shortening suggests reduced myofibril function in patients with hypertension‐induced hypertrophy 27 .…”
Section: Discussionmentioning
confidence: 99%
“…15 Several previous reports have compared intensivistperformed focused echocardiography to invasive hemodynamics, formal echocardiography, expert opinion, or interpretation by a cardiologist. 6,11,20,21,22 Each of these studies demonstrated that the study data obtained are comparable with their reference standard. Manasia et al reported the ability to perform a focused examination in 94% of their surgical ICU patients with 84% accuracy.…”
Section: Discussionmentioning
confidence: 72%